Changes in the Oropharyngeal Microbiome Preceding Ventilator-Associated Pneumonia. (4th October 2017) - Sommerstein, Rami; Merz, Tobias; Berger, Sabine; Mika, Moana; Marschall, Jonas; Hilty, Markus
Abstract: Background: We hypothesized that in ventilated patients the composition and the temporal evolution of the oropharyngeal microbiome may predict the development of ventilator-associated pneumonia (VAP). Methods: Prospective, observational single-center nested case–control study. Patients with acute critical illness and anticipated duration of mechanical ventilation >4 days were eligible. We took oropharyngeal swabs (and if available, tracheal secretions) on a daily basis, starting with the day of intubation. Microbiota were characterized with 16S rRNA pyrosequencing and compared between patients who developed VAP vs. controls. Results: Thirty patients met inclusion criteria and were enrolled, among which we selected 10 for microbiome evaluation. Five of them developed VAP. In three of those the causative pathogens were Enterobacteriaceae and in two Haemophilus influenzae (HI). The within diversity ( = alpha) decreased significantly throughout the first five days in Enterobacteriaceae VAP patients ( P = 0.002) but not in HI VAP patients ( P = 0.6) when compared with no VAP (Figure 1). When comparing the oral microbiomes in individual patients between the initial sample and day 4, the in-between diversities ( = β) were not different in patients with Enterobacteriaceae VAP, HI VAP or controls. Detection of Enterobacteriaceae in the oropharynx occurred on day two of follow-up and consisted of a single species in 2/3 patients (Figure 2). Conclusion: In patients who develop enterobacterial VAP the causative pathogen appears to gain access to the oropharynx early after starting ventilation and outgrow the commensal members of the microbiome. A decreased alpha diversity may contribute to the development of VAP pathogenesis, given that this was not witnessed in patients without VAP. Relative Abundance of causative (red) and any other Enterobacteriaceae (orange) is shown for individual patients (S x ). Results of paired oral and tracheobronchial (TBS) samples are shown according to the grid (upper right). Enterobacteriaceae VAP patients are shown in the upper part. Disclosures: All authors: No reported disclosures.